Food insecurity among Chinese households in Projek Perumahan Rakyat Air Panas, Setapak, Kuala Lumpur, Malaysia - Yong, P. P.; Sulaiman, Norhasmah (Community Health Society Malaysia, 2016)
Background: This study examines food security status among Chinese households in Projek Perumahan Rakyat (PPR) Air Panas, Setapak, Kuala Lumpur. Materials and Methods: A simple random sampling method was used to select 109 respondents. A Face-to-face interview was used to collect data on food security status and coping strategies related to food insecurity among the respondents. Radimer/Cornell Hunger and Food Insecurity Instrument was used to measure the household food insecurity. The Malaysian Coping Strategies Instrument (MCSI) items were used to measure the respondents’ coping strategies related to food insecurity. Results: The results showed that 50.6% of the Chinese households were in food insecurity status. About 91.4% of the households prefer to “use less expensive food” and 87.7% of the households prefer “buying less expensive products or shopping at cheaper place”. There were significant mean differences between age of respondents’ (p<0.01), number of household size (p<0.000), household income (p<0.05), number of children (p<0.000), number of schooling children (p<0.05), number of disable family members (p<0.000), respondent’s education (p<0.05), spouse education (p<0.05), food expenditure (p<0.05) and non-food expenditure (p<0.05) with food security status. There was also a significant mean difference between respondents’ anthropometric measurements with food security status (p<0.05). Conclusion: In conclusion, demographic and socioeconomic characteristics were contributed to household food insecurity. Meanwhile, overweight and obesity as well as at-risk to abdominal obesity were the consequences of food insecurity in this study. Further studies are suggested to conduct a comparative study in different geographic areas to understand broader aspects of food insecurity among Chinese households in Malaysia.